Godsdienstvrijheid onder druk? Reacties van levensbeschouwelijke organisaties in Nederland op het Zwitserse minarettenverbod - Wiegers, Gerard (Religie & Samenleving, 2012)
The freedom of religion which exists throughout Europe has not led to equal rights nor equal social acceptance of Muslims. This holds especially true for Islamic rituals and symbols such as the public call to prayer which only in the Netherlands has been accepted on national level after discussion in Parliament in the 1980s. That this right has only sporadically been effectuated is probably mainly due to the influence of increasing social pressures related to increasingly negative attitudes of the non-Muslim population since the 1980s and anti-Muslim political parties and a changing view on the public display of religious symbols. The same pressures appear from discussions about mosques in general and minarets in particular. This article discusses the reactions of 21 religious and humanist organisations in the Netherlands on the Swiss ban on minarets and argues that they show an awareness of an increasing pressure on the free exercise of this right. They all see the freedom to build minarets as a core element of freedom of religion on equal footing with the freedom to build other religious buildings (although they do not value minarets in the same way). Most of them denounce the proposal to prohibit or limit the freedom to build them as expressions of anti-Islamic views. However, their reactions show different appreciations and solutions to the pressure, ranging from outright rejection of any concessions to possible adaptation.